2011
DOI: 10.1007/s11164-011-0305-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of 1′,3,5,5′-tetramethyl-1′H-1,3′-bipyrazole on the corrosion of steel in 1.0 M hydrochloric acid

Abstract: The effect of some prepared compounds, namely 3,5-dimethyl-1H-pyrazole (P1), 3(5)-amino-5(3)-methylpyrazole (P2), and 1 0 ,3,5,5 0 -tetramethyl-1 0 H-1,3 0 -bipyrazole (P3), on the corrosion behaviour of steel in 1.0 M hydrochloric acid solution as corrosive medium has been investigated at 308 K using weight-loss measurement, potentiodynamic polarisation, linear polarisation, and impedance spectroscopy (EIS). Generally, inhibition efficiency of the investigated compounds was found to depend on the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 64 publications
(63 reference statements)
0
24
0
Order By: Relevance
“…The inhibiting effect of the bipyrazoles 12 and 93 was attributed to their adsorption at the metal-solution interface, owing to the presence of many active centers (several nitrogen atoms and many π-electrons of the pyrazole rings) for adsorption which revealed that inhibitive actions of bipyrazole compounds were mainly due to adsorption on steel surface. [170][171][172] The bipyrazole derivatives (bippyphos) 57 were applied as efficient ligands in the palladium-catalyzed C-O and C-N cross-coupling reactions of aryl halides with primary alcohols and with urea derivatives, respectively. 46,[173][174][175][176] 5,5'-Dihydroxy-4,4'-bipyrazoles 356 were reported as useful medicines for treatment of cerebral ischemia, heart diseases, gastrointestinal diseases, cancer, aging and inflammation.…”
Section: Scheme 99mentioning
confidence: 99%
“…The inhibiting effect of the bipyrazoles 12 and 93 was attributed to their adsorption at the metal-solution interface, owing to the presence of many active centers (several nitrogen atoms and many π-electrons of the pyrazole rings) for adsorption which revealed that inhibitive actions of bipyrazole compounds were mainly due to adsorption on steel surface. [170][171][172] The bipyrazole derivatives (bippyphos) 57 were applied as efficient ligands in the palladium-catalyzed C-O and C-N cross-coupling reactions of aryl halides with primary alcohols and with urea derivatives, respectively. 46,[173][174][175][176] 5,5'-Dihydroxy-4,4'-bipyrazoles 356 were reported as useful medicines for treatment of cerebral ischemia, heart diseases, gastrointestinal diseases, cancer, aging and inflammation.…”
Section: Scheme 99mentioning
confidence: 99%
“…They were used as supramolecular complexes, organometallic cage‐like structures, and self‐assembling metallo‐macrocycles that are promising as catalysts, molecular mimics, molecular magnetic devices, and sensors . Furthermore, some bipyrazole derivatives were used as inhibitors for the corrosion of steel and as bidentate ligands to form ruthenium(II) complexes for hydrogenation reactions . Bipyrazoles were also reported to have antitumor, anti‐inflammatory, and cytotoxic activities and are scavengers for free radicals .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a side chain on pyrazole showed an increase in the efficiency of the pyrazole and the longer the chain the higher the higher efficiency [21]. Several pyrazole derivatives were evaluated as steel corrosion inhibitors in our laboratory [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%